The icon and the square : Russian modernism and the Russo-Byzantine revival - Taroutina, Maria; Pennsylvania State University Press (University Park, Pennsylvania : The Pennsylvania State University Press, 2018)
"Charts the rediscovery and rigorous reassessment of the medieval Russo-Byzantine artistic tradition in Russia in the years 1860-1920. Explores the link between Byzantine revivalism and modernist experimentation, which ultimately made a significant and lasting impact on twentieth-century avant-garde movements"--Provided by publisher
Byzantium reconsidered : revivalism, avant-gardism and the new art criticism -- From Constantinople to Moscow and St. Petersburg : museums, exhibitions and private collections -- Angels becoming demons : Mikhail Vrubel's modernist beginnings -- Vasily Kandinsky's iconic subconscious and the search for the spiritual in art -- Towards a new icon : Kazimir Malevich, Vladimir Tatlin and the cult of non-objectivity.
Includes bibliographical references and index.
Print version record.
In English.
eBooks on EBSCOhost
Keywords: Art, Russian -- 19th century; Art, Russian -- 20th century; Art, Modern -- Byzantine influences; Modernism (Art) -- Russia; Art, Byzantine -- Influence; Art russe -- 19e siècle.; Art russe -- 20e siècle.; Modernisme (Art) -- Russie; Art byzantin -- Influence; ART -- History -- General; ART -- Russian & Former Soviet Union; Art, Byzantine -- Influence; Art, Modern -- Byzantine influences; Art, Russian; Modernism (Art); Russia; 1800-1999; Byzantine revival; Kandinsky; Kazimir; Malevich; Mikhail; Modern Art; Modernism; Revivalism; Russian art; Tatlin; Vasily; Vladimir; Vrubel; iconic revival; medieval revival